The Symbolic Interpretation of Quraish Shihab on The Hadith of Women's Creation - Majid, Abdul (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
The complete negation of misogynistic hadiths towards women is still not possible due to a textual and non-comprehensive understanding of the hadiths. This article aims to address this issue by presenting an analysis of Quraish Shihab's interpretation of the hadith regarding the creation of Eve from Adam's curved rib bone and differentiating his view from several other commentators. Using a literature review approach, this study shows that the term